Assessing the impact of syntactic complement type on the modifying status of complement-taking predicates: the case of imagine. (July 2021) - Maekelberghe, Charlotte
Abstract: The present study examines the grammaticalization potential of different syntactic complement types by means of a case study of the complement-taking predicate (CTP) imagine . Building on the assumption that CTP-clauses can be conceived of as embedded within a larger taxonomy of interrelated constructions at various levels of schematicity, it is argued that the development of grammatical variants with one complement type should also be viewed in relation to other complementation patterns realized by that predicate. Similarities and differences between complementation types were visualized by means of a hierarchical cluster analysis of 2000 instances of imagine from the Spoken BNC2014 corpus. It is shown that there is a distribution of labor between the complement types in terms of the structure and semantics of their respective CTP-clauses. Qualitative analyses furthermore confirm that only CTP-clauses with zero complementation meet all criteria for grammatical status, although interpersonal functions can also be found with other syntactic complement types. The exploitation of this interpersonal function, it is argued, may eventually also result in the grammaticalization of more formulaic units with imagine . Highlights: This paper examines the broader constructional network of the complement-taking predicate imagine. We find a distribution of labor between imagine CTP-clauses with different complement types in terms of mood and modality. CTP-clauses with zero complementation meet all criteria for grammatical status. Combinations with other syntactic complement types can develop into markers of intersubjectivity or interaction managers.